Some Notes on the Problems Surrounding the History of Isa-Bey’s Tekke - Aščerić, Ines (Prilozi za orijentalnu filologiju, 2017)
The primary aim of the article is to draw attention to some of the problems which relate to the history of Isa-bey’s tekke in Sarajevo and which emerge from the existing literature on the subject. The article points out that for the time being the most reliable source on this important building is Isa-bey’s wakfname from 1462, but that even \vith regard to the contents of this docu- ments the literature contains a number of inconsistencies, the most important of which relates to the size and layout of Isa-bey’s tekke. After an analysis of the text of Isa-bey’s wakfhame, the article concluđes that the edifice in question consisted of one building (and not two as implied in some works), which had three wings and which, according to the terms set out in the wakfname, was used both as a tekke and a musafirhane. The article further points out the existence of a number of problems regarding the identification of Isa-bey’s tekke with the Mevlevi tekke in Sarajevo, which is mentioned by a number of sources, and questions the generally accepted thesis - based primarily on Evliya Çelebi’s 17th century description of this Mevlevi tekke - that Isa-bey’s tekke grew into a major Mevlevi centre within the first two centuries of its existence. A more detailed analysis of this and other sources relating to the Mevlevi tekke shows that most of them cannot refer to Isa-bey’s tekke and that, therefore, linking every mention of Mevlevism in Sarajevo to Isa-bey’s tekke is unjustified. In con- clusion, while stili affirming the importance of Isa-bey’s tekke, the article nevertheless calls for a reconsideration of the existing theses on its history.